PEMANFAATAN MEDIA SOSIAL AUTOBASE TWITTER @COLLEGEMENFESS SEBAGAI PENCARIAN RESPONDEN DALAM PENELITIAN ONLINE DI LINGKUP PERGURUAN TINGGI - Marisa; Aini, Siti Nur (Prosiding Temu Ilmiah Nasional Guru, 2023)
This research aims to determine the use of autobase on Twitter as a researchrespondent search tool. In this research, a qualitative approach was used using the literaturestudy method. The results of this research show that the use of the autobase system on the@collegemenfess Twitter account really helps students collect their online research data.Autobase can be used without space and time limitations, minimizes research costs and providesdirect interaction features between respondents and researchers. However, there is a weaknessin the autobase system, namely that there is a buildup of messages and information due to thelarge number of messages sent at one time, so that the readability of messages by@collegemenfess followers is low. Another weakness of autobase is that researchers do not getrespondents according to the required characteristics. In addition, there was an exchange ofrespondents between researchers.